Meta Analisis Model Pembelajaran Collaborative Learning dalam Pembelajaran Bahasa Indonesia di SD - Sa'adah, Nalis; Nuryanto, Sukarir (YASIN, 2025)
The literacy skills of primary school students in Indonesia remain at a low level, highlighting the need for more innovative and participatory strategies in Bahasa Indonesia instruction. One promising instructional model is Collaborative Learning, which emphasizes social interaction and cooperation among students to build shared understanding. This study aims to quantitatively analyze the effectiveness of the Collaborative Learning model in Bahasa Indonesia instruction through a meta-analytical method. A total of seven quantitative studies meeting the inclusion criteria were analyzed using a random-effects model approach. The analysis yielded an average effect size of g = 1.20, categorized as very large, with a high level of heterogeneity (I² = 83.6%). These findings indicate that the Collaborative Learning model consistently has a positive impact on student learning outcomes and language skills, particularly in writing, speaking, and reading comprehension. Furthermore, publication bias analysis revealed no indications of selective reporting of significant results, reinforcing the validity of the findings. The study concludes that Collaborative Learning is an effective approach to enhancing foundational literacy among primary school students. Its implication is that this model should be widely integrated into Bahasa Indonesia instruction to support literacy development and the optimal implementation of the Kurikulum Merdeka.